EVALUASI PENGGUNAAN KOMPOSTER (TAKAKURA DAN DRUM) BANTUAN PEMERINTAH 01 INSTITUSI PENDIDIKAN SURABA YA TAHUN 2013 - Robithoh Wahyuliyanti; Darjati .; Irwan Sulistio (Poltekkes Kemenkes Surabaya, 2014)
Garbage is a wasted material that comes from human and nature activities. Processing of organicwaste in educational Institutions at Surabaya use composter. The purpose of research was evaluate theusing of goverment aid composter (takakura and drum) in educational Institutions at Surabaya. Thisresearch was eksploratory research. Data were collected by direct observation and interview. Sampleswere 40 educational Institutions at Surabaya. Data were analyzed descriptive statistics its were presentedin tabular form.The result were BO used takakura and 15 used drum. BO% officers had good level of knowledge, .75% officers had good attitude and 55% officers had good action. It is recommended to optimaze using ofcomposter